Evaluasi Kesesuaian Lahan Beberapa Tanaman Hortikultura dan Status Kesuburan Tanah di Kelurahan Banturung, Kecamatan Bukit Batu, Kota Palangka Raya - Pranata Wijaya, Gusti Indra; Damanik, Zafrullah; Susi, Theresia; Jemi, Renhart; Hastari, Belinda; Sudyana, I Nyoman (Universitas Pahlawan Tuanku Tambusai, 2023)
Evaluation of land suitability and soil fertility status is useful for assessing the potential of agricultural areas. This research aims to determine the physical, chemical properties, soil fertility status, factors that influence land suitability classes and land suitability classes (actual and potential), as well as to obtain improvements and directions for land use. This research is a qualitative descriptive study. Analyze data by matching land characteristics with land use. The research results show low soil fertility status. The limiting factors for land suitability classes are temperature (tc), water availability (wa), oxygen availability (oa), rooting media (rc), nutrient retention (nr), available nutrients (na), erosion hazard (eh) and danger flood (fh). The land suitability classes in SPT I-II are actually marginally suitable (S3) and in SPT III-VII are not suitable (N) and potentially in SPT I and II are quite suitable (S2) and very suitable (S1). Improvement efforts are carried out on land limiting factors. Land use directions are recommended in SPT I and SPT II.